Strategi Manajerial dalam Peningkatan Kompetensi Kader Posyandu melalui Pelatihan Stimulasi Perkembangan Bayi untuk Mencegah Global Development Delay - Ratnaningsih, Ester; Febriati, Listia Dwi; Sugathot, Aan Ika; Zakiyah, Zahrah (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Global developmental delays in toddlers are a major concern, with around 5-10% of toddlers experiencing this problem. At the Duku, Jampidan, Banguntapan, Bantul Regency Posyandu, only 40% of cadres have had training in infant development stimulation. Therefore, training for Posyandu cadres is very important to improve their competence in detecting and providing appropriate developmental stimulation. This community service program aims to provide training in infant developmental stimulation for Posyandu cadres, so that they can be better prepared to detect developmental delays early on. The training was conducted in August 2023 using a demonstration method by four lecturers and involved 22 participants. The results of the pretest evaluation showed that 45.5% of cadres had poor knowledge, while 54.5% had sufficient knowledge. After the training, the posttest results showed a significant increase in knowledge, with 90.9% of cadres having good knowledge, and 9.1% having sufficient knowledge. This program has succeeded in improving the competence of cadres in detecting and providing infant developmental stimulation.